Lateral approach for insertional Achilles tendinitis with Haglund deformity - Jiang, Jiantao; Wang, Cheng; Fu, Shaoling; Wang, Jiazheng; Wu, Chenglin; Yao, Guangxiao; Song, Guoxun; Gu, Wenqi; Yang, Kai; Xue, Jianfeng; Shi, Zhongmin (Frontiers in Surgery, 2023)
Objective:To investigate the the functional outcome of the lateral approach for insertional Achilles tendinitis (IAT) with Haglund deformity.Methods: From January,2016 to September, 2019,14 cases IAT with Haglund deformity recalcitrate to conservative treatment received surgery in our department. Lateral approach was used to debride the bony and soft tissue, and reattach the insertion of the Achilles tendon.The Visual Analogue Scale (VAS), American Orthopaedics Foot and Ankle Score (AOFAS) and Victorian Institute of Sport Tendon Study Group-Achilles Tendinopathy score (VISA-A) were used to evaluate clinical outcome. Result: The mean age was 39.57 years at the time of surgery. The mean follow-up was 14 months. The mean VAS score significantly decreased from 4.86±0.86 preoperatively to 1.21±1.58 postoperatively (p<0.0001). The mean AOFAS score significantly improved from 66.64±6.23 preoperatively to 90.21±11.50 postoperatively (p<0.0001). The mean preoperative and the last follow-up VISA-A were66 (range 56.75 to 69.25) points and 86(range 75.75 to 97.00) points, respectively(P<0.05) .Conclusion: the lateral Approach was effective and safe for insertional Achilles tendinitis with Haglund deformity. And the mid-term function outcome was promising.